(untitled) (Eurasian Research Bulletin, 2023)
Reducing energy consumption during pneumatic conveying cotton is a topical issue at the ginning plants. In this paper we consider the possibility of reducing energy costs by using smaller diameter pipes. It proposed a mathematical model and presents the analysis of energy consumption on parameters of the pneumatic conveyor and flow.